The Implementation of Asymmetric Fiscal Decentralization in Developing Non-Traditional Security in Papua - Hendy Setiawan; Yendra Erison; Choirunnisa Choirunnisa (Pusjar SKPP Lembaga Administrasi Negara, 2025)
This article aims to discuss the relevance of implementing asymmetric fiscal decentralization in building non-traditional security in Papua. For over two decades, Papua has had a special autonomy status. Under the legal basis of Law Number 21 of 2001 concerning Special Autonomy for Papua, which was followed in 2002 by the asymmetric fiscal decentralization policy of the Central Government, it provides space for Papua to improve and develop non-traditional forms of security that are more dynamic and welfare-oriented. This study uses a qualitative method with a documentary analysis approach. This study utilizes accurate document data, which is analyzed using existing techniques. The results of the study indicate that the asymmetric fiscal decentralization policy has not been fully implemented in developing non-traditional forms of security (human security). This was identified as an area where numerous human security problems persist, ranging from unfulfilled food needs to a weak social life within society, including poverty and low human development. All of which are markers that such security problems are a nontraditional threat to Papua. Therefore, the state must review the special autonomy policy that can create non-traditional security and is oriented towards the welfare of Papua